2008
DOI: 10.1097/nen.0b013e318186de48
|View full text |Cite
|
Sign up to set email alerts
|

Lewy Body Pathology Involves Cutaneous Nerves

Abstract: Involvement of the peripheral autonomic nervous system is a core feature of Lewy body (LB) diseases, including Parkinson disease (PD), PD with dementia, and dementia with LBs. To investigate the potential use of skin biopsy for the diagnosis of LB diseases, we assessed anti-phosphorylated alpha-synuclein immunoreactivity in peripheral nerves in samples of skin from the abdominal wall and flexor surface of the upper arm in 279 prospectively studied consecutively autopsied patients whose data were registered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
138
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(143 citation statements)
references
References 28 publications
3
138
2
Order By: Relevance
“…Cardiac sympathetic denervation occurs at early stages of disease [21,22]. A recent study showed α-SYN inclusions in skin sympathetic nerve fibers of patients who had Lewy body pathology in the central nervous system and adrenal medulla [24].…”
Section: Sympathetic Systemmentioning
confidence: 98%
“…Cardiac sympathetic denervation occurs at early stages of disease [21,22]. A recent study showed α-SYN inclusions in skin sympathetic nerve fibers of patients who had Lewy body pathology in the central nervous system and adrenal medulla [24].…”
Section: Sympathetic Systemmentioning
confidence: 98%
“…This may be explained by methodologic differences. 4,5 Our skin biopsies were fixed in Zamboni solution for only 18 hours because we find loss of immunostaining after 24 hours. Other studies have used fixation in 4% paraformaldehyde for 48 hours, a process frequently used in CNS immunohistochemistry, but not in peripheral nerves where prolonged fixation causes rapid degradation of nerve fibers and loss of immunofixation.…”
Section: Figurementioning
confidence: 99%
“…[4][5][6][7][8] We recently reported novel methods to study the cutaneous autonomic innervation in skin biopsies of patients with peripheral nerve disease.…”
mentioning
confidence: 99%
“…In postmortem tissues, pSNCA has been detected in skin samples from the upper extremities, abdomen and scalp (Ikemura et al, 2008;Beach et al, 2010). In vivo studies assessing skin pSNCA deposits have reported on the presence of SNCA aggregates in patients with Parkinson's disease, with variable frequencies ranging from 0% to 100% (Wang et al, 2013;Donadio et al, 2014;Navarro-Otano et al, 2014), probably in part because different sites were selected for the skin biopsy.…”
mentioning
confidence: 99%